Use of Learning Facilities on Students' Islamic Religious Education Learning Achievement in High School - Ilyas, Khusnul Khatimah; Beglerovic, Samir; Atique, Tareque Bin (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: Learning facilities are all the lessons students need in the learning process so that the learning process can run well, but in this research it only focuses on textbook learning facilities. This research aims to determine the learning achievement of Islamic Religious Education students in high school using textbooks. Methodology: The type of research used is field research with a qualitative approach, while the research design is qualitative descriptive research. The type of research and data sources used are primary data and secondary data. Data collection techniques used include observation, interviews and documentation to obtain reported values. Main Findings: The results of this research show that the use of Islamic Religious Education learning process textbooks is very effective and the Islamic Religious Education learning achievement of class XI students in high school is in the very good category. Novelty/Originality of this study: The integration of technology such as the use of learning software, educational applications, and interactive hardware in teaching Islamic Religious Education can provide a more interesting and effective learning experience for students. Leverage online resources such as instructional videos, interactive materials, and distance learning platforms to increase accessibility and variety in instruction.